Penerapan Genre-Based Approach pada Pembelajaran Bahasa Inggris Di SDN Ngaliyan 01 Semarang: Analisis Genee dalam Buku Kurikulum Merdeka pada Fase B - Hidayat, Rima Aulia; Purwati, Kristi Liani; Amin, Muhammad Zuhdi (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2024)
This study analyzes the implementation of the Genre-Based Approach (GBA) in teaching English to 3rd and 4th graders in Phase B of the Merdeka Curriculum at SDN Ngaliyan 01 Semarang. The research aims to identify the genres used in textbooks and evaluate their contribution to students' comprehension. A qualitative descriptive method was employed, collecting data through classroom observation and textbook analysis. The findings reveal that descriptive, narrative, and procedural genres effectively enhance students' understanding of the material. Visual media, such as images and short videos, play a significant role in simplifying abstract concepts and increasing student engagement. Engagement levels reached 85% in the 4th grade, with comprehension rates up to 80%. However, challenges such as limited teaching time and varying student abilities were addressed through interactive, visual-based strategies. This study highlights the relevance of GBA in supporting students' literacy and provides recommendations to further enhance its application with more innovative, media-supported approaches aligned with the Merdeka Curriculum.